The Quality of Life of Patients with HIV/AIDS Undergoing Antiretroviral Therapy: A Systematic Review - Putri Irwanti Sari; RTS Netisa Martawinarti; Nurmawati S. Lataima; Vivi Meiti Berhimpong (Jurnal Ners, 2019)
Introduction: Quality of Life (QoL) is one of the most important things for a patient with HIV/AIDS. Good QoL will improve the adherence to treatment, especially antiretroviral therapy. The purpose of this study was to explore about the quality of life of the patients with HIV/AIDS undergoing antiretroviral therapy.Methods: The data was collected through a literature review from electronic databases such as Scopus, ProQuest, Google Scholar and Springerlink journal. The keywords were "quality of life", "HIV/AIDS", "quality of life of patients with HIV/AIDS" or "quality of life and HIV/AIDS and antiretroviral therapy".Results: The researcher obtained 15 articles based on the inclusion criteria. Several research articles that were analyzed showed that the Quality of Life of HIV/AIDS patients undergoing antiretroviral therapy was not all good. This is caused by the side-effects of using antiretroviral therapy and the side-effects that were physical, psychological, social and environmental.Conclusion: The impact of the side effects of antiretroviral therapy has caused the clients with HIV/AIDS to choose other therapies such as ART replacement therapy to improve the quality of life for patients with HIV/AIDS.